Answer:
x = 1
Step-by-step explanation:
Expand brackets
2x + 16 - 4x = 10x + 4
Rearrange so that x's are on one side and whole numbers are on the other
2x - 4x - 10x = 4 - 16
Simplify
-12x = -12
Make x on its own
x = 1
Answer:
(4,12)
(-1,-3)
Step-by-step explanation:
x^2 - y = 4
y = 3x
Use substitution. Substitute 3x for y in the first equation
x^2 - (3x) = 4
x^2 -3x =4
Subtract 4 from each side
x^2 -3x -4 = 4-4
x^2 -3x-4 =0
Factor
(x-4) (x+1) =0
Using the zero product property
x-4 =0 x+1 =0
x=4 x=-1
Now to find y for each x solution
x=4
y =3x = 3(4) =12
(4,12)
x=-1
y =3x = 3(-1) =-3
(-1,-3)
Answer:
Yes plz!
Step-by-step explanation:
The total is found by adding all of the numbers together! the total is 1335
<h2>Hello There today we will solve your equation</h2>
Here are the graphs